2021
DOI: 10.1038/s41598-021-92357-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal outcomes and risk factors for COVID-19 severity among pregnant women

Abstract: Pregnant women may be at higher risk of severe complications associated with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which may lead to obstetrical complications. We performed a case control study comparing pregnant women with severe coronavirus disease 19 (cases) to pregnant women with a milder form (controls) enrolled in the COVI-Preg international registry cohort between March 24 and July 26, 2020. Risk factors for severity, obstetrical and immediate neonatal outcomes were assessed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
2
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 37 publications
4
88
2
6
Order By: Relevance
“…11 A large international study also demonstrated that the presence of diabetes, hypertension and pulmonary disease were risk factors for COVID-19 infection during pregnancy. 12 In summary, the incidence of COVID-19 does not appear to be higher in pregnancy.…”
Section: Maternal Demographicsmentioning
confidence: 86%
See 1 more Smart Citation
“…11 A large international study also demonstrated that the presence of diabetes, hypertension and pulmonary disease were risk factors for COVID-19 infection during pregnancy. 12 In summary, the incidence of COVID-19 does not appear to be higher in pregnancy.…”
Section: Maternal Demographicsmentioning
confidence: 86%
“…An increased rate of preterm birth, low birth weight, pre-eclampsia, and Cesarean delivery has been described with COVID-19. 6,8,12,18 Among pregnant individuals with COVID-19 who delivered in Canada, 97% of births were live births, 63% were vaginal deliveries, and 37% were Cesarean sections driven by obstetrical, fetal, or medical indications. 6 The rate of preterm birth was 12.3% in pregnant individuals with COVID-19, which is higher than the pre-pandemic period (8.3% baseline rate).…”
Section: Obstetrical and Neonatal Outcomesmentioning
confidence: 99%
“…Although our understanding is still evolving, available data strongly suggests pregnant people with COVID-19 infection experience a higher severity of illness and increased rates of complications compared to age-matched non-pregnant patients; neonatal morbidities are also increased. ( 2 , 3 , 4 , 5 , 6 , 7 , 8 ) Effective prevention and treatment strategies are therefore critically important to improve maternal and neonatal outcomes but, regressive policies excluding pregnant people from participating in biomedical research persist. ( 9 , 10 ) Clinicians and pregnant people are left with the difficult task of deciding whether potential benefits of a treatment outweigh potential harms to the fetus based on very little information.…”
Section: Discussionmentioning
confidence: 99%
“…( 2 , 3 , 4 , 5 , 6 ) In addition, COVID-19 has been associated with increased preterm birth and neonatal morbidities. ( 2 , 3 , 5 , 6 , 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, among infected women of the reproductive age range (ages 12-51), it was found that pregnant women in this range were more likely to be hospitalized and admitted into the Intensive Care Unit (ICU) as compared to non-pregnant women in the same range, but both non-pregnant and pregnant women had a similar chance for death ( Ellington et al., 2020 ; Zambrano et al., 2020 ). Since pregnant women are considered to be vulnerable to SARS-CoV-2 infection, it is essential to understand if the virus could infect the developing fetus ( Panagiotakopoulos et al., 2020 ; Brandt and Fell, 2021 ; Vivanti et al., 2020a ; Vouga et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%